Draft Annual Plan 1972-73 Volume I Government of Bihar - Planning Commission (Planning Commission, 1972)
With the formal ending of the 3rd Plan in March,1966 and annual plans for the 3 successive years, the 4th Five Year Plan was launched from 1969-70. Financial target of the Fourth Five Year Plan was kept at Rs.531.28 crores, which included the Central assistance of 338 crores. The progressive totals of outlay for the 3 years should have been Rs.285.92 crores or 54% of the total outlay but it is likely to be only Rs.228.69 chores which is only 43% of the total outlay. the progressive achievement for the 4th year and the 5th year should be Rs.412.61 crores.
Planning Department Government of Bihar